A case study of Tadao Ando's Church of the Light and the Eychaner/Lee : the traditional Japanese sense of 'Ma' and 'Oku', and its reinterpretation in contemporary architecture - Wang, Hai (Kansas State University, 2003)
This thesis seeks to present the traditional Japanese sense of space, Ma and Oku, and explore how these two vernacular concepts are reinterpreted and manipulated by Tadao Ando in two recent works: the Church of the Light and the Eychaner/Lee House. In light of Ma and Oku, this thesis generates four categories in terms of center and periphery, nature and geometry, materiality and immateriality, space and time for the case study of the two buildings. This study intends to identify the underlying design concepts and principles that engender the two works with an architectural expression relating to the traditional sense of ma and oku. The prime focus of this thesis is to examine Ando's methodology in his reinterpretation of the traditional concept Ma and Oku within a contemporary context, an approach Ando considers as his criticism on Western Modernism and contemporary consumerism. This thesis concludes that, by rethinking the Japanese traditional spatial sensibilities Ma and Oku while reinterpreting them in virtue of the vocabulary developed by an open and universal modern architecture, Ando opens a new horizon to modern architecture that is critical on two interrelated counts: it constitutes an architecture centered on regional cultural identity in opposition to universal Modernism, and it establishes a microcosmic domain for substantial existence in opposition to contemporary consumerism on the other. Ando's architectural ideology is to resort to tradition while being wedged in contemporary circumstance, and to participate in the modern world while not being absorbed by it. Ultimately, the originality and individuality of Ando's works are perceived and articulated in the gap between the East and the West, between culture and civilization.
Department: Architecture.